THE IMAGE OF FLAX IN FOLKLORE AND LITERATURE: PSKOV AND LATGALE FRONTIER - Razumovska, Aīda (Via Latgalica, 2017)
The article presents reflections on flax as a floral symbol of Pskov land and Latgale. The folklore of neighbouring lands describes how flax was grown, processed and used for ritual purposes as a protective charm against negative energy. The semantics of flax reflects the archaic character of the homeland in the cultural knowledge of the people of the Pskov-Latgale frontier and their loyalty to tradition.Flax has always been the main field plant and source of income in frontier lands of Pskov and Latgale. In the world market the most valuable flax among all other types of Baltic and Belorussian flax was Pskov flax fibre.In the flax growing territories long-lasting folklore traditions were set up, which indicates that flax has always had not only practical but also a symbolic meaning for the peoples of the Baltic States, Belarus and Russia. In the territory of Pskov region the crop fertility rites were practised to ensure the flax crops, for example, horse riding for “tall flax”. Flax fibre was considered to be an amulet, a protection from negative energy. Flax linen sheets were used during childbirth in Latgale, in Pskov land the afterbirth was wrapped in it and given to the midwife; the sick children were wrapped up in the flax prayer tablecloth, etc.In Russian folklore in the territory of Latgale flax growing and flax processing are frequently reflected in couplets (chastushkas), riddles and lyrical songs. Flax is the symbol of strength and persistence. Numerous contacts on frontier territories have contributed to the plot commonalities of fairy and non-fairy prose, e. g. flax can save man from the evil spirit. Such plots are registered both in the territory of Pskov region and Latgale. The image of flax left the realm of folklore for literature, which is common for both Pskov and Latgale.Latvian poets create a vivid image of “flax crop fields” which reflect the landscape peculiarity of Latgale. Quite often the image of flax crop fields brings them back the memories about their past life (V. Krāslavietis, P. Antropov – O. Alekseyev). So V. Krāslavietis remembers his native Latgale with the blue lakes, where blue flax is growing, where he rides to visit someone on a horse of cheerful memories. Flax often takes Pskov writers on a journey into the memory (O. Alekseyev, L. Malyakov).There is an inseparable link of flax with the landscape of Latgale and with the people living there. A. Kūkojs marks parallelism in his daughter’s appearance: curly and thin as Latgalian flax is daughter’s hair. Pskov poet O. Alekseyev uses such comparisons to reveal the power and tenderness of the folk soul.At the same time flax is associated with human character and soul of people, who are known for such typical traits as hard work and holiness, sufferings and belief. Purity and tenderness of flax corresponds to the shyness of Latgalian girls (Madsolas J.). Latgale is portrayed as a barefoot “orphan girl” who endures patiently life hardships “under the grey woolen sky” among “the fields covered with flax stalks” (A. Kūkojs).For the Russian writers (immigrants who used to live in Pskov land and were attracted to it and associated Pskov with Russia) flax symbolizes unbreakable bond of times and loyalty to the traditions of Pskovites (L. Zurov). The image of flax in literature can be not only visual but olfactory as well. Poet Y. Ivask recalls Pskov with its “retted autumn flax”. Stinking smell, “repelling, but healing stench” has the highest spiritual value for the homesick poet. Not the beauty of the blue flax but its repelling stench is taken by the poet as a gift – as it cleanses the spirit.For Pskov writers of the second half of the 20th century flax field also symbolises the Motherland (S. Zolotsev, E. Borisov, A. Аbrosimov) – “golden” and happy, despite the grief periods. The flax field causes them to contemplate, feel tenderness and sadness. The loss of flax, which is the floral symbol of the native land, has been lately regarded by our contemporaries as a break with traditions and oblivion of the past (Е. Еrmak).Flax in the literature of Pskov and Latgale is the symbol of the Motherland. It acts as a human being and embodies natural beauty and persistence. In Latgalian poetry the image of flax supports the myth about people who suffer or are orphans, who are hardworking and selfless. In Pskov literature flax depicts fading patriarchal character of the native land; no wonder Pskov is called the land of “flaxen Rus” (V. Sergeyeva).